Effect of Turbulence over a Submerged Cylinder of Aluminium Alloy 7075 - Manish Kumar Rawat (International Journal of Advanced Science and Technology, 2020)
High velocity Flow with different velocity profile around a flat (2D) streamlined cylinder of aluminium alloy 7075, is simulated by using k- ε turbulence model. The estimation of the effect of velocity on key variables like drag force and separation point along the outer surface of flat 2D aluminium alloy cylinder is the main motive of this study. Most air planes are made up of aluminium alloy with stream line shape because of its high strength, low weight and drag coefficient as compare to other materials. The force on a circular aluminium alloy cylinder is greater than that of an elliptical cylinder. The rate of reduction in drag force can be increased by varying the alloying elements and reducing the axis ratio with the same aluminium alloy material. The reduction in drag force is due to the forward movements of points of separations which is affected by the smoothness of the surface and streamline profile.